2018
DOI: 10.23851/mjs.v29i2.345
|View full text |Cite
|
Sign up to set email alerts
|

ERIC- PCR Typing, RAPD-PCR Fingerprinting and Quorum Sensing Gene Analysis of Pseudomonas aeruginosa Isolated from Different Clinical Sources

Abstract: Recently, Pseudomonas aeruginosa infections proportions have increased significantly. Molecular typing and virulence analysis are good techniques, which can lead us to know P. aeruginosa infections. P. aeruginosa isolates were identified by using molecular method (16S rDNA gene) via PCR technique for accurate identification. The highest percent 41.26% of P. aeruginosa bacteria was found in the burn infections followed by 28.57% in wound swabs, 17.46% in ear discharge and lowest percentage were obtained from sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…RAPD-PCR, a method designed to investigate the genetic differences of bacteria isolated from different sources, is based on various primers and reaction conditions and as a method it is easy to do and cost-effective for large number of isolates (Hilton et al, 2006). In study conducted by Sallman et al (2018) in Iraq, they found that 61 P. aeruginosa strains isolated from different clinical cases showed changing similarity rates between 25-92% with RAPD-PCR. In a study conducted by Ozturk et al…”
Section: Discussionmentioning
confidence: 99%
“…RAPD-PCR, a method designed to investigate the genetic differences of bacteria isolated from different sources, is based on various primers and reaction conditions and as a method it is easy to do and cost-effective for large number of isolates (Hilton et al, 2006). In study conducted by Sallman et al (2018) in Iraq, they found that 61 P. aeruginosa strains isolated from different clinical cases showed changing similarity rates between 25-92% with RAPD-PCR. In a study conducted by Ozturk et al…”
Section: Discussionmentioning
confidence: 99%
“…Current findings revealed local isolates carrying one or more QS genes. The Iraqi study conducted by Sallman et al (2018) reported 82.53% isolates carrying lasI/lasR and rhlI/rhlR genes. Senturk et al (2012) displayed that 77.7%, 88.8%, 66.6%, and 77.7% of isolates were positive for rhIR, rhlI , lasR, and lasI, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These observations agree with other authors who mentioned that P. aeruginosa is present in about 33% of burn wounds and 59% of extensive burns. Huebinger RM et al 16 and Sallman RS et al 17 noticed that P. aeruginosa was obtained from 41.26% burn infection, followed by 28.57% wound swabs. In this study, it was noticed that the lowest percentage of isolation was from vaginal swab 1/50 (2%), followed by blood samples 1/50 (2%).…”
Section: Discussionmentioning
confidence: 99%